2014
DOI: 10.1016/j.yexcr.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional ECM proteins in bone and teeth

Abstract: The extracellular matrix (ECM) of all tissues and organs is a highly organized and complex structure unique to the specific organ type. The ECM contains structural and functional proteins that define cellular function, organization, behavior and ultimately organ characteristics and function. The ECM was initially thought to contain only a specific set of secretory proteins. However, our group and several other groups have shown that the ECM contains functional proteins that have been previously defined as sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…We were particularly encouraged to note the increased expression of DPP and DMP1 along the interface of the soft tissue and dentin. DPP and DMP1 are key regulators of matrix mineralization and odontogenic differentiation [54]. Therefore, their expression at the interface of the pulp dentin complex is indicative of enhanced odontogenic differentiation and reparative dentin formation.…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly encouraged to note the increased expression of DPP and DMP1 along the interface of the soft tissue and dentin. DPP and DMP1 are key regulators of matrix mineralization and odontogenic differentiation [54]. Therefore, their expression at the interface of the pulp dentin complex is indicative of enhanced odontogenic differentiation and reparative dentin formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, odontoblasts are surrounded by collagen and dentin matrix proteins. A recent report has demonstrated that ECM, especially the dentin matrix protein component, contains functional proteins that have been previously defined as solely intracellular (19). However, DMP-1, which has a role in matrix mineralization, can act as both an intra-and extracellular-signaling molecule, thus impacting odontoblast differentiation (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The key strategy for successful periodontal regeneration requires the stimulation of MSC-derived PDLSCs (Seo et al, 2004). In addition, recent studies have established that multifunctional ECM proteins regulate cell behavior (Rozario et al, 2010;Ravindran et al, 2014), and that modulated stem cell migration contributes to the initial process of tissue regeneration (Sonoyama et al, 2006). While the cellular responses to amelogenin, an ECM-biocompatible protein, in PDL fibroblasts have been examined Cheng et al, 2012), the key signaling molecules and effects on PDLSCs have yet be completely defined.…”
Section: Discussionmentioning
confidence: 99%